Heme oxygenase 1 polymorphism, occupational vapor, gas, dust, and fume exposure and chronic obstructive pulmonary disease in a Danish population-based study - Würtz, Else Toft; Brasch-Andersen, Charlotte; Steffensen, Rudi; Hansen, Jens Georg; Malling, Tine Halsen; Schlünssen, Vivi; Omland, Øyvind (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVES ': 'The number of dinucleotide repeats (GT)n modulate expression of heme oxygenase 1 (HMOX1), a stress response gene. Multiple repeats might affect chronic obstructive pulmonary disease (COPD) susceptibility. We aimed to investigate the association of this polymorphism with COPD and its interaction with occupational exposures (vapor, gas, dust, or fumes). ' ' METHODS ': 'This population-based cross-sectional study included 4703 Danes, aged 45–84 years. HMOX1 (GT)n was genotyped and grouped as short: ≤26, medium: 27–32 and long: ≥33 alleles. COPD was defined by the lower limit of normal (2.5th FEV1/FVC and FEV1 centiles). Occupational exposure was defined as ever exposed to vapor, gas, dust, or fume in expert-selected jobs. Associations were analyzed by adjusted mixed logistic regression. ' ' RESULTS ': 'The population included 6% with COPD, 48% who had smoked ≥10 pack-years, and 46% with occupational exposure. HMOX1 was genotyped in 4423 participants. The adjusted odds ratio (OR) for the association between HMOX1 long allele and COPD was 1.75 [95% confidence interval (CI) 1.18–2.60]. An interaction was evident between HMOX1 long allele and occupational exposure, OR 2.38 (95% CI 1.04–5.46), versus HMOX1 short/medium without exposure. Analyses were replicated in another cohort, aged 20–44 years, N=1168, including 3% with COPD, 25% who had smoked ≥10 pack-years and 20% with occupational exposure. No associations were seen between COPD and HMOX1 long allele here. ' ' CONCLUSIONS ': 'Long alleles in HMOX1 alone and in interaction with occupational exposure seem to be associated with COPD. Failure to replicate data may be due to premature age for COPD development and low occupational exposure prevalence. We propose this long allele may be a genetic contributor to the COPD pathogenesis.
Keywords: chronic obstructive pulmonary disease; COPD; Denmark; dust; dust exposure; exposure; fume; fume exposure; gas; gas exposure; gene-by-occupational interaction; genetic effect; heme oxygenase 1 polymorphism; HMOX1; lung function; occupational exposure; population-based study; rs3074372; vapor; vapor exposure